From West Africa to West Indies: the Movement of German and Italian Internees in the British Empire during World War II, 1939-45 - Muojama, Olisa Godson (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
Wars lead to disruptions in the relationships of the belligerent countries. As soon as hostilities are declared, all interactions between citizens of hostile territories cease. The declaration of a state of war culminates in a prohibition of commercial intercourse between the subjects of the contending powers. It also leads to the proscription and unpleasant treatments of the citizens of the hostile countries. This study, therefore, examines the treatment of the enemy aliens in British Empire during the Second World War, with a special focus on the transfer of the German and Italian internees from Nigeria in West Africa to Jamaica in West Indies. It also deals with the representations by several individuals and agencies in connection with the internees in Jamaica, as well as their enlistment in the British Auxiliary Military Pioneer Corps. Archival sources provide data for this historical reconstruction. It is a contribution to knowledge in the areas of Second World War, German Studies, treatment of the enemy aliens, and the place of West Africa in the historiography of World War II. Keywords: German/Italian Internees, Prisoners of War, West Africa, West Indies, British Empire, Second World War